2017
DOI: 10.1111/ppa.12656
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Xanthomonas perforans race T4 causing bacterial spot in tomato breeding lines

Abstract: Tomato (Solanum lycopersicum) is the second most important vegetable crop in the world. Bacterial spot (BS) of tomato, caused by four species of Xanthomonas: X. euvesicatoria, X. vesicatoria, X. perforans and X. gardneri, results in severe loss in yield and quality due to defoliation and formation of lesions on fruits, respectively. Currently management practices do not offer effective control under conditions of high disease pressure. Thus, developing BS resistance is a critical priority for tomato growers in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…There have been many types of researches on finding resistance to diseases like bacterial spot; however, no single cultivar has been developed that can resist all races of Xanthomonas causing bacterial spot making this disease a very difficult problem to overcome [34]. This explains the low correlation of bacterial spot with any other traits observed in this study as seen in a previous study [35], whereas resistance to fungal diseases like early blight, late blight, fusarium, and verticillium wilts and nematode resistance have been identified and are already being introgressed in new varieties [36].…”
Section: Discussionmentioning
confidence: 99%
“…There have been many types of researches on finding resistance to diseases like bacterial spot; however, no single cultivar has been developed that can resist all races of Xanthomonas causing bacterial spot making this disease a very difficult problem to overcome [34]. This explains the low correlation of bacterial spot with any other traits observed in this study as seen in a previous study [35], whereas resistance to fungal diseases like early blight, late blight, fusarium, and verticillium wilts and nematode resistance have been identified and are already being introgressed in new varieties [36].…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to X. euvesicatoria pv. perforans race T4 in tomato breeding lines was reported by Bhattarai et al (2017). Stall et al (2009) described the progress in the cloning of avirulence genes and identification of resistance-related genes in tomato and pepper over the past several decades.…”
Section: Novel Achievements In Host Resistance Developmentmentioning
confidence: 99%
“…Bhattarai, et al [42] reported the moderate level of resistance against race T4 in S. pimpinellifolium derived breeding lines, including 74L-1W (2008), NC2CELBR, 081-12-1X-gsms, NC22L-1 (2008), and 52LB-1, in the field and greenhouse studies. Further work is needed to characterize the resistance observed in these lines and to evaluate if the observed resistance in these lines is sufficient to manage the disease before integrating the resistance in the cultivar.…”
Section: Genetics and Breeding Efforts To Improve The Bs Disease Resimentioning
confidence: 99%